2009
DOI: 10.1016/j.jtcvs.2008.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prior percutaneous coronary intervention on the outcome of coronary artery bypass surgery: A multicenter analysis

Abstract: Multicenter analysis confirms that a history of multiple previous percutaneous coronary interventions increases in-hospital mortality and the incidence of major adverse cardiac events after subsequent coronary artery bypass grafting. Critical discussion of the treatment strategy in these patients is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 29 publications
6
65
3
1
Order By: Relevance
“…As consequence, there are an increasing number of patients who have been submitted to PCI with stents before being finally referred for CABG. In the literature, this incidence ranges from 10% to 20% [8][9][10] . From our study group, 161 patients (14.6%) had previous PCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As consequence, there are an increasing number of patients who have been submitted to PCI with stents before being finally referred for CABG. In the literature, this incidence ranges from 10% to 20% [8][9][10] . From our study group, 161 patients (14.6%) had previous PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown restenosis rates after PCI with stent, with need of reintervention due to symptom recurrence, ranging from 20% to 40% 6,7 . More recently, it has been discussed whether previous PCI is a risk factor with negative impact on the outcomes of CABG [8][9][10] . A significant inflammatory process and endothelial function abnormalities in the coronary arteries have been related to the treatment with stent, especially when drug-eluting stents were used [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, in the study of Lisboa et al previous PCI emerged as an independent predictor of in-hospital mortality as strong as diabetes [7]. Some of the studies also indicate that multiple PCIs are stronger predictor of the above-mentioned clinical endpoints compared to single previous PCI or no prior PCI [11,12]. Except for the impact of prior PCI on perioperative mortality, Bonaros et al reported higher perioperative morbidity (MACE, bleeding complications, acute renal failure, renal replacement therapy and the use of blood products) as well [6].…”
Section: Discussionmentioning
confidence: 99%
“…Although, there is a large body of evidence indicating that previous PCI adversely affects clinical outcomes of CABG, this is not supported by other published data [5,6,7,8,9,10]. Some studies reported that patients with multiple PCI procedures have significantly increased risk for in-hospital mortality and major adverse cardiac events (MACE) compared with patients without or with only a single previous PCI [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, contemporary results for CABG following PCI are characterized by worse perioperative outcomes when compared with CABG patients without previous intervention. For example, higher rates of postoperative mortality, MACE, and other perioperative complications following CABG in both diabetic and nondiabetic patients have been observed [47][48][49][50]. More importantly, increased mid-term mortality in diabetic patients with prior PCI has been observed after CABG [50], and Rao et al demonstrated increased long-term mortality in patients with prior PCI who subsequently underwent CABG [51].…”
Section: Comparing Coronary Bypass Surgery and Pcimentioning
confidence: 99%